(untitled) (Proceedings of the Society of Antiquaries of Scotland, 2013)
Recent regeneration works in the east end of Glasgow prompted Forestry Commission Scotland to re-evaluate their landholdings at Cuningar Loop, north-east of Rutherglen. This paper explores Cuningar Loop’s hidden past as a key location in the wider early 19th-century attempt to furnish Glasgow’s ever-expanding population with water. Using historical sources, it examines how a committee of influential citizens established, managed and implemented the project. It also explores how the committee relied on the great engineers of the time, in particular, Thomas Telford and James Watt, to deliver the project using cutting edge technology which ultimately proved inadequate. This sheds light upon the network of social relations revealed by the correspondence of the protagonists, and explores the physical legacy of these early engineers in a city where these pioneering works have been eclipsed by the later Victorian scheme to draw potable water from Loch Katrine.